Upaya Guru Tahfidz Dalam Meningkatkan Kualitas Hafalan Al-Quran Pada Santri Tahfidz Di Pondok Pesantren Ibn Jauzi - Siti Rahma Bahrin (UMSU, 2022)
The purpose of this study is to find out how the efforts of tahfidz teachers in improving the quality of memorizing the Qur'an in tahfidz students and what are the obstacles and solutions. The method in this research is a field study approach using qualitative research. It was carried out at the Ibn Jauzi Islamic boarding school from January to March 2022. The primary data were tahfidz teachers, and secondary data were the head of the foundation and tahfidz students, the validity of the data was done by triangulation of sources, the data was obtained by observation and in-depth interviews, then the data was analyzed descriptively with Miles and Huberman's theory. The results of this study indicate that the efforts of tahfidz teachers in improving the quality of memorizing the Qur'an of students are carried out by: emphasizing intentions, motivating students, murojaah continuously and talaqqi in front of the teachers. The obstacles are; the age of the students, the physical condition of the students, the lack of motivation, the physical condition of the teachers, and the feeling of laziness in the tahfidz students. The solution is done by; conduct evaluations, provide continuous motivation, and provide extra supervision.